"HELLO, I'M A NATIVE SPEAKER": NONNATIVE TUTORS' PERSPECTIVES ON NATIVE-SPEAKERISM IDEOLOGY - Ronald Maraden Parlindungan Silalahi; Nugraheni Widianingtyas (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Native-speakerism is an ideology in foreign language teaching that believes that Native English Speaking Teachers (NESTs) have better competencies than Nonnative English Speaking Teachers (NNESTs). There are marked differences between NESTs and NNESTs in private classroom learning; for instance, the hourly fees of NESTs are much higher than NNESTs regardless of the long language teaching career. More importantly, there is hardly any research on Native-speakerism ideology from the perspective of nonnative English private tutors. This research, therefore, is conducted to give a broader conception of how NNESTs perceive the native-speakerism ideology in a private class context and contribute to the relatively unexplored area of language teaching. The data of this qualitative study were obtained through a small-scale interview with nonnative English private tutors. Results show that private learning, based on the informants' standpoints, is more oriented to making speakers able to use language skills to communicate fluently than to understand the target language culture, which NNESTs may not fully comprehend. The identity as a NEST and NNEST insignificantly affects tutors' linguistic and teaching competence. However, it significantly creates a massive gap in the teaching costs despite most NESTs' lack of classroom management skills and communication effectiveness to explain teaching materials due to language barriers.